2006
DOI: 10.1161/circulationaha.105.561449
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Cathepsin K Gene Reduces Atherosclerosis Progression and Induces Plaque Fibrosis but Accelerates Macrophage Foam Cell Formation

Abstract: Background-Cathepsin K (catK), a lysosomal cysteine protease, was identified in a gene-profiling experiment that compared human early plaques, advanced stable plaques, and advanced atherosclerotic plaques containing a thrombus, where it was highly upregulated in advanced stable plaques. Methods and Results-To assess the function of catK in atherosclerosis, catK Ϫ/Ϫ /apolipoprotein (apo) E Ϫ/Ϫ mice were generated. At 26 weeks of age, plaque area in the catK Ϫ/Ϫ /apoE Ϫ/Ϫ mice was reduced (41.8%) owing to a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
157
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(173 citation statements)
references
References 43 publications
12
157
0
1
Order By: Relevance
“…ApoE:cathepsin K double knockout mice had reduced atherosclerotic lesions together with increased collagen component of ECM, whereas apoE-and LDL receptor-deficient mice that were given TGF-␤ inhibitors had decreased vascular ECM and more plaque hemorrhages. [31][32][33] In our study, losartan nearly doubled the relative collagen portion of the lesions. Although these results seem to be at odds with effects of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers to limit ECM deposition in nonatherogenic disorders, they echo observations made in other models of atherosclerosis, including the Watanabe heritable hyperlipidemic rabbits and atherosclerotic mini-pigs, in which angiotensin-converting enzyme inhibitors/angiotensin receptor blockers increased ECM, including collagen, in the aortas.…”
Section: Discussionsupporting
confidence: 59%
“…ApoE:cathepsin K double knockout mice had reduced atherosclerotic lesions together with increased collagen component of ECM, whereas apoE-and LDL receptor-deficient mice that were given TGF-␤ inhibitors had decreased vascular ECM and more plaque hemorrhages. [31][32][33] In our study, losartan nearly doubled the relative collagen portion of the lesions. Although these results seem to be at odds with effects of angiotensin-converting enzyme inhibitors and angiotensin receptor blockers to limit ECM deposition in nonatherogenic disorders, they echo observations made in other models of atherosclerosis, including the Watanabe heritable hyperlipidemic rabbits and atherosclerotic mini-pigs, in which angiotensin-converting enzyme inhibitors/angiotensin receptor blockers increased ECM, including collagen, in the aortas.…”
Section: Discussionsupporting
confidence: 59%
“…D, F, S and K) modify apolipoprotein B in LDL and subsequently induce foam cell formation 15) . Moreover, a study of catK − /apoE − mice showed a trend toward increased serum cholesterol and LDL cholesterol levels 16) .…”
Section: Ctss Mrna Quantification In the Plasmamentioning
confidence: 99%
“…Yet because of the involvement in a variety of pathological conditions of the cardiovascular and pulmonary systems, degradation of aorta and lung elastins is of particular interest. All three cathepsins showed highest activity against aorta elastin when compared with elastins from other sources, and cathepsin K activity was more than 2-fold larger than that of cathepsins L and S. Multiple studies have described the involvement of these cathepsins in the degradation of elastic fibers of blood vessel walls in vivo, which contributes to the development of pathological conditions such as atherosclerosis, aortic aneurysms, stenosis, and heart failure (22)(23)(24)(25)(26)(27)(28)(29)(30). In contrast, cathepsin K showed very little activity in degrading lung elastin, but cathepsin L was the most efficient enzyme in degrading this substrate, with activity comparable with that observed with aorta elastin.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have implicated cathepsins K, L, and S, as well as some others, in extensive degradation of elastic fibers, which accompanies the development of pathological conditions of the cardiovascular system. In mice, cathepsin S was found to co-localize with regions of increased elastin breakdown in atherosclerotic plaques (22), and reduced atherosclerosis was observed in cathepsin S-and K-deficient mice (23,24). In rats, up-regulation of cathepsin S and K activity was also observed following carotid artery injury (25).…”
mentioning
confidence: 99%